STRATEGY SURVIVELY IN THE MIDDLE OF UNCERTAINITY PANDEMI COVID-19 MARITIME SECTOR BUSINESS - Hadi Prasutiyon; R.O Saut Gurning (Universitas Trunojoyo Madura, 2020)
The Covid-19 pandemic crisis of 2020, different from previous crisis / disasters, given the uncertainty, no one can predict or look ahead, when the end of this crisis is over. Global impact that touches almost all sectors and is directly related personally and family. Fast-moving events, we talk day by day, with a situation that is changing and unprecedented. This requires us to make policies, responses and rapid mitigation of impacts on shared covid-19. Management policies must reach the infrastructure, work and engagement sectors required to be fast and appropriate. In dealing with such situations, it is necessary to apply crisis management, so that the main things that must be prioritized can be found. The government is expected to provide fiscal incentives, especially to national companies, in the form of tax breaks, small loans, or other assistance. So that the company can survive to avoid layoffs and be able to rise again after going through this crisis.